Efficacy and safety of erdafitinib in patients with locally advanced or metastatic urothelial carcinoma: long-term follow-up of a phase 2 study. Issue 2 (February 2022) - Siefker-Radtke, Arlene O; Necchi, Andrea; Park, Se Hoon; García-Donas, Jesús; Huddart, Robert A; Burgess, Earle F; Fleming, Mark T; Rezazadeh Kalebasty, Arash; Mellado, Begoña; Varlamov, Sergei; Joshi, Monika; Duran, Ignacio; et al.
Summary: Background: Erdafitinib, a pan-fibroblast growth factor receptor (FGFR) tyrosine kinase inhibitor, was shown to be clinically active and tolerable in patients with advanced urothelial carcinoma and prespecified FGFR alterations in the primary analysis of the BLC2001 study at median 11 months of follow-up. We aimed to assess the long-term efficacy and safety of the selected regimen of erdafitinib determined in the initial part of the study. Methods: The open-label, non-comparator, phase 2, BLC2001 study was done at 126 medical centres in 14 countries across Asia, Europe, and North America. Eligible patients were aged 18 years or older with locally advanced and unresectable or metastatic urothelial carcinoma, at least one prespecified FGFR alteration, an Eastern Cooperative Oncology Group performance status of 0–2, and progressive disease after receiving at least one systemic chemotherapy or within 12 months of neoadjuvant or adjuvant chemotherapy or were ineligible for cisplatin. The selected regimen determined in the initial part of the study was continuous once daily 8 mg/day oral erdafitinib in 28-day cycles, with provision for pharmacodynamically guided uptitration to 9 mg/day (8 mg/day UpT). The primary endpoint was investigator-assessed confirmed objective response rate according to Response Evaluation Criteria In Solid Tumors version 1.1. Efficacy and safety were analysed in all treated patients who received at least one dose of erdafitinib. This is the final analysis of this study. This study is registered with ClinicalTrials.gov, NCT02365597 . Findings: Between May 25, 2015, and Aug 9, 2018, 2328 patients were screened, of whom 212 were enrolled and 101 were treated with the selected erdafitinib 8 mg/day UpT regimen. The data cutoff date for this analysis was Aug 9, 2019. Median efficacy follow-up was 24·0 months (IQR 22·7–26·6). The investigator-assessed objective response rate for patients treated with the selected erdafitinib regimen was 40 (40%; 95% CI 30–49) of 101 patients. The safety profile remained similar to that in the primary analysis, with no new safety signals reported with longer follow-up. Grade 3–4 treatment-emergent adverse events of any causality occurred in 72 (71%) of 101 patients. The most common grade 3–4 treatment-emergent adverse events of any cause were stomatitis (in 14 [14%] of 101 patients) and hyponatraemia (in 11 [11%]). There were no treatment-related deaths. Interpretation: With longer follow-up, treatment with the selected regimen of erdafitinib showed consistent activity and a manageable safety profile in patients with locally advanced or metastatic urothelial carcinoma and prespecified FGFR alterations. Funding: Janssen Research & Development.